Spectrophotometric Determination of Bromhexine Via Ion-Pair Complex Formation with Eosin Y: Method Development, Validation, and Pharmaceutical Application - Younes, Samer Rafeh; Ahmed, Iman Diab (American Journal of Biomedicine and Pharmacy, 2025)
A simple, rapid, and reliable spectrophotometric method was developed for the quantitative determination of bromhexine hydrochloride (BRH) in bulk and pharmaceutical formulations. The process is based on the formation of a stable purple ion-pair complex between BRH and Eosin Y dye, which exhibited maximum absorbance at 550 nm. Experimental conditions, including dye concentration, pH, temperature, and reaction time, were systematically optimized to achieve maximum sensitivity. Under the established conditions, the calibration curve showed excellent linearity over the concentration range of 30–100 µg/mL with a correlation coefficient (r²) of 0.999. Analytical validation demonstrated high accuracy (recovery 97.7–103.7%) and precision (RSD ≤ 1.9%), with limits of detection (LOD) and quantification (LOQ) of 0.1449 and 0.4391 µg/mL, respectively. The proposed method was successfully applied to the analysis of commercial bromhexine syrup (Solvodin), with satisfactory recovery and reproducibility. A stoichiometric study revealed a 1:1 molar ratio of drug to dye in the formed complex. Compared with existing spectrophotometric methods, the developed approach offers improved sensitivity and reliability. The technique is simple, cost-effective, and suitable for routine quality control of bromhexine in pharmaceutical industries.